Chronic immune thrombocytopenic purpura - Rodeghiero, F.; Ruggeri, M. (Hämostaseologie, 2009)
First generation thrombopoietic growth factors (rhTPO and PEG-rHuMGDF), investigated in the early 2000s, proved effective in increasing platelet count in normal volunteers, in thrombocytopenia due to chemotherapy and also in a few cases of immune thrombocytopenic purpura (ITP). These agents did not complete their clinical development since one of them induced antibodies in the recipients that cross reacted with endogenous thrombopoietin (TPO), thus causing thrombocytopenia. This promoted the ingenious design of a new generation of thrombopoietic growth factors having no sequence homology with natural TPO. The two main agents are romiplostim, a peptibody already approved for clinical use in USA and eltrombopag, a non-peptide, orally active small molecule. In open label and placebo-controlled trials both agents proved to predictably increase platelet count in normal volunteers and in patients with ITP. With appropriate dosages (1–10 µg/kg weekly sub cutaneously for romiplostim; 50–75 mg/die per os for eltrombopag ) a platelet increase becomes significant after 7–10 days and peaks between 10–14 days. By dis -continuing treatment, platelet count returns to baseline level in 10–15 days. The response rate with both agents is above 70–80%, also in patients that had undergone several lines of treatment, or that have failed splenectomy. The response is maintained during the treatment, but is almost invariably lost even after several months of successful administration. Due to the lack of a curative potential and to the incomplete knowledge of long-term side effects, the place of these new drugs in the management of ITP is still unsettled and their use is best restricted to refractory patients or in preparation of splenectomy. It seems however that a new paradigm in the treatment of ITP has been established where the focus is not on reducing platelet consumption but on increasing platelet production.
Keywords: Immune thrombocytopenia; thrombopoietin receptor agonist; therapy